Representing the 1909 Adana Massacres in Armeno-Turkish: Garabed Artinian and the Case for a Historical Reading - Matossian, Bedross Der (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
This article concentrates on the literary representation of the Adana Massacres of 1909. While most of the material lamenting these massacres was written in Armenian, this article deals with a rare and unpublished destan (lamentation poem) of the massacres in Armeno-Turkish. The author, Garabed Artinian, penned the longest destan that has existed on the massacres. Unlike a historical narrative, the destan is a poetic way of expressing sorrow and pain for the loss of lives, belongings, humanity, and honor. Artinian who witnessed both waves of the Adana Massacres in April, lost his wife and child, described in detail the unfolding of the horrifying crime. Artinian’s destan, which is made up of fifty-seven stanzas, was written in the third person in a lyrical style, while delivering a chronological account of the massacres. He experienced these events first-hand and thus through his destan Artinian ventured to “speak” the “unspeakable.” He wrote it to bear witness to the catastrophe. Hence, the destan is a work of art, a work of testimony, and an expression of pain and sorrow at the same time. The result achieved at least three things: a striking lamentation written in Armeno- Turkish about an incomprehensible catastrophe, a record and reconstruction of the trajectory of the events that transpired, written almost in real time, and a personal expression of pain and anguish by a survivor and witness to the massacres and their aftermath. Therefore, the destan has literary as well as historical value and should be treated as a uniquely informative source and expression. Through entering in dialogue with literary theories of the representation of the catastrophe and trauma studies, this article argues that the destan has literary as well as historical value and should be treated as a uniquely informative source and expression.
Keywords: Adana Massacres; Genocide